Orthodontic and surgical management of impacted teeth - Kokich, Vincent G.; Mathews, David P. ([S.l.] : Quintessence Publishing Co, Inc., 2019)
Impacted teeth are a commonplace encounter in dental practice, yet currently there is not a comprehensive book detailing the surgical treatments and orthodontic therapy to erupt or manage these teeth. Written by arguably the best orthodontist in the world and his periodontist colleague of almost 40 years, this text covers the various types of impactions an orthodontist and surgeon will encounter, including maxillary central incisors, maxillary canines (both labially and palatally impacted), mandibular canines, premolars, and mandibular molars. Each chapter focuses on a specific impacted tooth and how it can be surgically uncovered and orthodontically moved. The book also presents a chapter on failed cases, explaining what went wrong and how to prevent such negative outcomes when treating similar cases. Ideal for any dental practitioner who treats impacted teeth, this comprehensive and up-to-date book is a fitting legacy for Dr Kokich, whose impact within the field of orthodontics will be felt for years to come.
Orthodontic and surgical management of impacted teeth -- Contents -- Preface -- Chapter 1: Impacted Maxillary Central Incisors -- Chapter 2: Labially Impacted Maxillary Canines -- Chapter 3: Palatally Impacted Canines -- Chapter 4: Impacted Mandibular Canines -- Chapter 5: Impacted Premolars -- Chapter 6: Impacted Mandibular Molars -- Chapter 7: Complications and Adverse Sequelae -- Index -- About the Authors.
Includes bibliographical references and index.
Keywords: Tooth, Impacted -- surgery; Dentistry; General